2021
DOI: 10.33457/ijhsrp.854266
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Gender Perceptions of Nursing and Midwifery Students

Abstract: The culture of the society in which the individual lives determines the characteristics revealing the expectations about how a woman or a man behave, think and act, that is, structuring woman and man socially. This study was carried out to determine gender perceptions of nursing and midwifery students. Descriptive design type was used in the study. The universe of the study consisted of 750 students studying in Nursing and Midwifery Departments in 2018-2019. The sample consisted of 471 students who were not w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…(p=0,001). Numerous research undertaken within our nation have consistently revealed that female students exhibit greater levels of gender role attitudes or perceptions compared to their male counterparts [23][24][25][26][27]. The study conducted by Özpulat examined a sample of 247 university students and found that female students exhibited higher gender perception ratings in comparison to their male counterparts [21].…”
Section: *P<01mentioning
confidence: 99%
“…(p=0,001). Numerous research undertaken within our nation have consistently revealed that female students exhibit greater levels of gender role attitudes or perceptions compared to their male counterparts [23][24][25][26][27]. The study conducted by Özpulat examined a sample of 247 university students and found that female students exhibited higher gender perception ratings in comparison to their male counterparts [21].…”
Section: *P<01mentioning
confidence: 99%